International Working Group on Price Indices − The Ottawa Group : Proceedings of the Eight Meeting Helsinki, August 2004 - Koskimäki, Timo; Ylä-Jarkko , Mari (Statistics Finland, 2006)
In August 2004 Statistics Finland hosted the 8th meeting of the Ottawa Group, the international working group on price indices. This publication contains the post-conference fi nal versions of the papers that were presented in the meeting as well as the session summaries prepared by the session moderators. In addition to this publication, these papers will in the future also be available through the Ottawa Group web-site www.ottawagroup.org.
Keywords: tilastot; hinnat; indeksit